A simple mechanism for the roommate problem - Bora Evci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
Gale and Shapley (1962) proposed that there is a similar game to the marriage problem called "the roommate problem". And, they showed that unlike the marriage problem, the roommate problem may have unstable solutions. In other words, the stability theorem fails for the roommate problem. In this paper, we propose a new mechanism for the roommate problem. The mechanism is successful in determining the reason of instability in our game scenario. And, we show that our mechanism implements the full set of stable matchings in the existence of stability, and it ends up with Pareto Optimal matching in the instance of instability.
Keywords: C78; D71; D78; 330